Management of Recruitment of New Students in Improving The Quality of Reading and Writing Al-Qur’an - Siti Salbiyah; Sigit Priyosembodo (JOSSE: Journal of Social Science and Economics, 2022)
Management of student recruitment is an arrangement or arrangement of all processes to get potential potential students in accordance with the provisions to enter at a certain level of education. Management of the recruitment of new students is a must in the process of selecting potential students, so that students can take part in madrasa programs and have a high level of success, especially success in improving the quality of Al-Quran reading and writing. To find out about this, researchers conducted research on the success tips of MTs Diponegoro in improving the reading and writing quality of the Koran. The focus of the problem in this study is how to manage the recruitment of new students in improving the reading and writing quality of the Koran at MTs Diponegoro Plandaan. This type of research is descriptive qualitative. The data that has been obtained by the researcher will be analyzed qualitatively and described according to the results of the data that have been obtained. The data taken were PPDB 2021 activities and the results of learning to read and write the Koran for seventh grade students for one semester. The results of this study reveal that the efforts of MTs Diponegoro Plandaan Jombang in improving the reading and writing quality of the Koran, namely by organizing management in recruiting new students with various strategies and innovations and providing teachers according to educational qualifications, and using the At Tartil learning method in learning to read and write Al Qur'an by grouping teaching activities to facilitate coaching so that students are able to fulfill several indicators for each level with the assessment standards set by MTs Diponegoro Plandaan Jombang so as to produce quality graduates, especially the quality of reading and writing the Koran. Among the assessment standards set by MTs Diponegoro Plandaan to determine the quality of Al-Quran reading and writing in their madrasah is that students can read the Al-Quran correctly and fluently according to the rules of tajwid science and can correct wrong readings and can write Al-Quran letters (hijaiyah) correctly and neat or at least the writing is clear when read